1995
DOI: 10.1111/j.1432-1033.1995.tb20430.x
|View full text |Cite
|
Sign up to set email alerts
|

The MADS-Box Family of Transcription Factors

Abstract: The MADS-box family of transcription factors has been defined on the basis of primary sequence similarity amongst numerous proteins from a diverse range of eukaryotic organisms including yeasts, plants, insects, amphibians and mammals. The MADS-box is a conserved motif found within the DNA-binding domains of these proteins and the name refers to four of the originally identified members: MCM1, AG, DEFA and SRF. Several proteins within this family have significant biological roles. For example, the human serum-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
412
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 692 publications
(416 citation statements)
references
References 129 publications
2
412
0
2
Order By: Relevance
“…These observations, together with the accumulating data suggesting that MADS-box gene products typically inter-act with other proteins (Davies et al, 1996;Egea-Cortines et al, 1999;Fan et al, 1997;Shore and Sharrocks, 1995), suggested that AP1 and CAL may share a common set of protein partners, and that additional proteins may interact speci®cally with AP1. Using the yeast two-hybrid assay, we found that AP1 and CAL can each interact with a shared set of proteins, including SEP3, SOC1, SVP and AGL24.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These observations, together with the accumulating data suggesting that MADS-box gene products typically inter-act with other proteins (Davies et al, 1996;Egea-Cortines et al, 1999;Fan et al, 1997;Shore and Sharrocks, 1995), suggested that AP1 and CAL may share a common set of protein partners, and that additional proteins may interact speci®cally with AP1. Using the yeast two-hybrid assay, we found that AP1 and CAL can each interact with a shared set of proteins, including SEP3, SOC1, SVP and AGL24.…”
Section: Discussionmentioning
confidence: 93%
“…Remarkably, with the exception of the AP2 gene, all the other organ-identity genes belong to the extended family of MADS-box genes, a family that is known to include more than 44 distinct sequences in Arabidopsis (Alvarez- Buylla et al, 2000a;Davies and Schwarz-Sommer, 1994;Purugganan et al, 1995;Rounsley et al, 1995). MADS-domain proteins, well characterized in yeast (MCM1, Ammererer, 1990) and mammals (SRF, Norman et al, 1988), form dimers that bind to DNA and form ternary complexes with many unrelated proteins (Lamb and McKnight, 1991;Shore and Sharrocks, 1995). A number of studies have shown that heterodimers and ternary complexes of plant MADS-domain proteins can occur and, given the overlapping expression pattern of numerous MADS-box genes, such interactions greatly increase the regulatory complexity of MADS-box genes (Davies et al, 1996;Egea-Cortines et al, 1999;Fan et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the two proteins have overlapping binding sequences in MyoD-SMB. Second, no interaction is possible between two different members of the MADS-box family (for review, see Shore and Sharrocks, 1995), and we found no evidence of interaction (by coimmunoprecipitation) in differentiated myotube extracts (our unpublished observations). Third, SRF and MEF2 proteins compete for binding to MyoD-SMB element ( Figure 4A).…”
Section: Myod-smb Element Is a Unique Hybrid Sequence Capable Of Bindmentioning
confidence: 93%
“…Because SRF interacts with DNA by point contacts with the helix minor groove and MEF2 with the major groove of DNA (Mueller and Nordheim, 1991;Wynne and Treisman, 1992), both factors could, in principle, occupy the SMB site simultaneously. However, interactions between the two members of the MADS-box family have not been described previously (our unpublished data; Shore and Sharrocks, 1995). The steric hindrance of high molecular weight (MW) complexes associated with either SRF (L'honore et al, 2003) or MEF2 (ϳ600 kDa; our unpublished observation) suggests a mutually exclusive binding of SRF-and MEF2-containing complexes to SMB element.…”
mentioning
confidence: 85%